Korelasi Tingkat Pengetahuan Terhadap Keberhasilan Terapi Pasien Hipertensi di Puskemas - Tuti Wiyati; Vera Rahayu; Septianita Hastuti (UIN Syarif Hidayatullah Jakarta, 2023)
Knowledge can affect the success of therapeutic outcomes in hypertensive patients. Blood pressure must be controlled to prevent risk factors for other cardiovascular diseases. The purpose of this study was to analyze the relationship between knowledge of patients with hypertension and the success of therapy outcomes that showed controlled blood pressure. This observational cross-sectional study was conducted from March to June 2021 at Tangerang District Health Centers. A sample of 85 outpatients with hypertension was administered the HK-LS questionnaire to measure their level of knowledge, while the results of therapeutic outcomes were measured using blood pressure. The results showed that 60% of patients had intermediate knowledge and only 28.24% of the subjects had well-controlled blood pressure. There was a correlation between knowledge and therapy outcomes (p<0.05) with coef. correlation was -0.336, means a weak and inverse correlation. Comorbidity and sex were significantly correlated with knowledge (p<0,05). The level of knowledge needs to be improved to decrease the number of comorbidities or risk of complications to raise the goal of therapy.